Early marriage in Malaysia / Mohamad Danish Jaffri… [et al.] - Jaffri, Mohamad Danish; Azman, Anis Irdina; Mohamad Rashidi, Nur Qirana Nabila; Mohd Riduan, Nur Farah Iryanti (Faculty of Communication & Media Studies, 2019)
Early marriage is defined as the marriage between two people in which one or both parties are younger than 18 years of age. Early marriages are also an option for parents as they can protect their daughter's dignity. In addition, many parents agree to marry their daughter at a young age due to financial problems and so on, so they trust the men who will marry their daughter to take care of her. There are two types of early marriage. The first is because of parents' coercion, and the second is because of their own will. But for today's early marriage has become a trend for young people. This study involved 421 respondents who answered the questionnaires that had been distributed. The questionnaire are about the acceptance of public towards early marriage.